(3CfXeI eMGSHI GdJcGdja GdeMOOI ebOeG (B:s (3fXGe GdJcGdja GdJbOjQjI hfXGe GdJcGdja GdeYjGQjI (B/s - (3GHQGgje, eMehO CMeOs; (3SGWY, QRhbs ((3YeGf(B: s (3eDSSI GdhQGb ddfTQ hGdJhRjY(B, s, 2001)
(3GdEWGQ GdYGe dhXjaI GdQbGHI Ydi GdJcGdja, GSJNOGe GSdhH GdJcGdja GdJbOjQjI aj GdQbGHI Ydi GdJcGdja, GSJNOGe fXGe GdJcGdja GdeYjGQjI aj GdQbGHI Ydi GdJcGdja, GLQGAGJ JMOjO hJMdjd GfMQGaGJ YfGUQ GdJcGdjas
(3GdeQGLY U(B.399s
Keywords: (3eMGSHI GdJcGdjas